2005
DOI: 10.1163/156854005774445519
|View full text |Cite
|
Sign up to set email alerts
|

A new species of the genus Ilyograpsus, I. vanninii sp. nov. (Brachyura, Grapsidae) from Somalia

Abstract: A new species of the genus Ilyograpsus,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Japanese I. nodulosus has been recorded from western Japan, including Wakayama, the Seto Inland Sea, and the Shikoku, Kyushu, and Ryukyu Islands (Komai & Wada, 2008), but their records are limited, and the species has been designated as near threatened (Japanese Association of Benthology, 2012). Only morphological descriptions of I. nodulosus and its larvae have been reported (Fukuda, 1978;Sakai, 1983;Sawada et al, 2005;Naruse & Kishino, 2006;Komai & Wada, 2008), and no study has reported on their ecological traits. The purposes of this study were to characterize the ecological traits of this species, such as life history and behavior, and compare them with other ocypodoids allied to the genus Ilyograpsus, such as species of Macrophthalmi-dae and Camptandriidae.…”
Section: Introductionmentioning
confidence: 99%
“…Japanese I. nodulosus has been recorded from western Japan, including Wakayama, the Seto Inland Sea, and the Shikoku, Kyushu, and Ryukyu Islands (Komai & Wada, 2008), but their records are limited, and the species has been designated as near threatened (Japanese Association of Benthology, 2012). Only morphological descriptions of I. nodulosus and its larvae have been reported (Fukuda, 1978;Sakai, 1983;Sawada et al, 2005;Naruse & Kishino, 2006;Komai & Wada, 2008), and no study has reported on their ecological traits. The purposes of this study were to characterize the ecological traits of this species, such as life history and behavior, and compare them with other ocypodoids allied to the genus Ilyograpsus, such as species of Macrophthalmi-dae and Camptandriidae.…”
Section: Introductionmentioning
confidence: 99%